Retained bullet fragments after nonfatal gunshot wounds: epidemiology and outcomes. Issue 6 (26th June 2021) - Nee, Nadya; Inaba, Kenji; Schellenberg, Morgan; Benjamin, Elizabeth R.; Lam, Lydia; Matsushima, Kazuhide; Strumwasser, Aaron M.; Demetriades, Demetrios
Abstract : BACKGROUND: With no consensus on the optimal management strategy for asymptomatic retained bullet fragments (RBF), the emerging data on RBF lead toxicity have become an increasingly important issue. There are, however, a paucity of data on the magnitude of this problem. The aim of this study was to address this by characterizing the incidence and distribution of RBF. METHODS: A trauma registry was used to identify all patients sustaining a gunshot wound (GSW) from July 1, 2015, to June 31, 2016. After excluding deaths during the index admission, clinical demographics, injury characteristics, presence and location of RBF, management, and outcomes, were analyzed. RESULTS: Overall, 344 patients were admitted for a GSW; of which 298 (86.6%) of these were nonfatal. Of these, 225 (75.5%) had an RBF. During the index admission, 23 (10.2%) had complete RBF removal, 35 (15.6%) had partial, and 167 (74.2%) had no removal. Overall, 202 (89.8%) patients with nonfatal GSW were discharged with an RBF. The primary indication for RBF removal was immediate intraoperative accessibility (n = 39, 67.2%). The most common location for an RBF was in the soft tissue (n = 132, 58.7%). Of the patients discharged with an RBF, mean age was 29.5 years (range, 6.1–62.1 years), 187 (92.6%) were me, with a mean Injury Severity Score of 8.6 (range, 1–75). One hundred sixteen (57.4%) received follow-up, and of these, 13 (11.2%) returned with an RBF-related complication [infection (n = 4), pain (n = 7), fracture nonunion (n = 1), and bone erosion (n = 1)], with a mean time to complication of 130.2 days (range, 11–528 days). Four (3.4%) required RBF removal with a mean time to removal of 146.0 days (range, 10–534 days). CONCLUSION: Retained bullet fragments are very common after a nonfatal GSW. During the index admission, only a minority are removed. Only a fraction of these are removed during follow-up for complications. As lead toxicity data accumulates, further follow-up studies are warranted. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III.